The antiproliferative activity of all-trans-retinoic acid catabolites and isomers is differentially modulated by liarozole-fumarate in MCF-7 human breast cancer cells. - Van heusden, J. (Nature Publishing Group, 1998)
The clinical use of all-trans-retinoic acid (ATRA) in the treatment of cancer is significantly hampered by the prompt emergence of resistance, believed to be caused by increased ATRA catabolism. Inhibitors of ATRA catabolism may therefore prove valuable for cancer therapy. Liarozole-fumarate is an anti-tumour drug that inhibits the cytochrome P450-dependent catabolism of ATRA. ATRA, but also its naturally occurring catabolites, 4-oxo-ATRA and 5,6-epoxy-ATRA, as well as its stereoisomers, 9-cis-RA and 13-cis-RA, show significant antiproliferative activity in MCF-7 human breast cancer cells. To further elucidate its mechanism of action, we investigated whether liarozole-fumarate was able to enhance the antiproliferative activity of ATRA catabolites and isomers. Liarozole-fumarate alone up to a concentration of 10(-6) M had no effect on MCF-7 cell proliferation. However, in combination with ATRA or the ATRA catabolites, liarozole-fumarate (10(-6) M) significantly enhanced their antiproliferative activity. On the contrary, liarozole-fumarate (10(-6) M) was not able to potentiate the antiproliferative activity of the ATRA stereoisomers, most probably because of the absence of cytochrome P450-dependent catabolism. Together, these findings show that liarozole-fumarate acts as a versatile inhibitor of retinoid catabolism in that it not only blocks the breakdown of ATRA, but also inhibits the catabolic pathway of 4-oxo-ATRA and 5,6-epoxy-ATRA, thereby enhancing their antiproliferative activity.